Analysis of the relationship between some indicators of sustainable development and economic growth in Iraq for the period (2004-2020) - Awad, Khalid Rokan; Abbas, Sami Hamed; Obed, Muhannad Khalifa (Revenue Journal: Management and Entrepreneurship, 2023)
The research aims to analyze the relationship between some indicators of sustainable development and economic growth, as well as knowing the extent of the impact of sustainable development indicators on the economic growth indicator represented by the gross domestic product in Iraq, through the use of time series to express the nature of the relationship between the variables of the study, and through estimation and analysis Relationship In the applied side in which the ARDL model was used, it was found that there is a long-term equilibrium relationship between some indicators of sustainable development and economic growth in Iraq, in addition to that indicators of sustainable development have an impact on economic growth in Iraq. The study, which means that sustainable development has contributed in one way or another to achieving economic growth in Iraq.